Herdenking in 'De Dwarsligger' (IJmuiden). Getoonde foto: De Jong-Lagerwaard (midden), De Winter (daarachter)
Herdenking in 'De Dwarsligger' (IJmuiden). Getoonde foto: De Jong-Lagerwaard (midden), De Winter (daarachter).